Design and test of target-oriented profile modeling of unmanned aerial vehicle spraying - Qi, Peng; He, Xiongkui; Liu, Yajia; Ma, Yong; Wu, Zhiming; Wang, Jianwo (International Journal of Agricultural and Biological Engineering, 2022)
Unmanned aerial vehicles (UAVs) are a new frontier in specialized plant protection equipment, which will increasingly be utilized in modern sustainable agricultural applications. The use of UAVs retrofitted with new structures for spraying allows precision pesticide applications on fruit canopies, which have positive effects on pesticide reduction, along with fruit quality and production improvement. In this work, a precision toward-target device (BUAV) was established through profiling of fruit branch modeling, along with a quality analysis of the coverage in a pear orchard compared to a conventional multi-rotor UAV (CUAV). Coverage under different canopy sections and on both sides of leaves was evaluated using Polyvinyl Chloride card samplers. The results indicate that coverage of the BUAV was 0.98% and 1.41% on the abaxial of the lower leaves interior of the canopy, which was 2.38 and 3.14 times higher than that of the CUAV. The BUAV tended to increase coverage in the course-parallel direction, while both the course-parallel and vertical directions increased the deposition coverage on the abaxial side of the interior canopy leaves by 1.8 times and 2.1 times compared to the CUAV, respectively. Simultaneously, the BUAV increased the proportion of droplets deposited on the canopy and reduced ground loss. The BUAV can improve the distribution of the wind field within the canopy effectively and improve the droplet deposition on the reverse side of the interior bore blade.Keywords: UAV, droplet coverage, target pesticide application, leaf abaxial side, profile spraying, orchardDOI: 10.25165/j.ijabe.20221503.6753Citation: Qi P, He X K, Liu Y J, Ma Y, Wu Z M, Wang J W. Design and test of target-oriented profile modeling of unmanned aerial vehicle spraying. Int J Agric & Biol Eng, 2022; 15(3): 85–91.